Rasagiline effects on glucose metabolism, cognition, and tau in Alzheimer's dementia. Issue 1 (14th February 2021) - Matthews, Dawn C.; Ritter, Aaron; Thomas, Ronald G.; Andrews, Randolph D.; Lukic, Ana S.; Revta, Carolyn; Kinney, Jefferson W.; Tousi, Babak; Leverenz, James B.; Fillit, Howard; Zhong, Kate; Feldman, Howard H.; et al.
Abstract: Background: A Phase II proof of concept (POC) randomized clinical trial was conducted to evaluate the effects of rasagiline, a monoamine oxidase B (MAO‐B) inhibitor approved for Parkinson disease, in mild to moderate Alzheimer's disease (AD). The primary objective was to determine if 1 mg of rasagiline daily for 24 weeks is associated with improved regional brain metabolism (fluorodeoxyglucose–positron emission tomography [FDG‐PET]) compared to placebo. Secondary objectives included measurement of effects on tau PET and evaluation of directional consistency of clinical end points. Methods: This was a double‐blind, parallel group, placebo‐controlled, community‐based, three‐site trial of 50 participants randomized 1:1 to receive oral rasagiline or placebo (NCT02359552). FDG‐PET was analyzed for the presence of an AD‐like pattern as an inclusion criterion and as a longitudinal outcome using prespecified regions of interest and voxel‐based analyses. Tau PET was evaluated at baseline and longitudinally. Clinical outcomes were analyzed using an intention‐to‐treat (ITT) model. Results: Fifty patients were randomized and 43 completed treatment. The study met its primary end point, demonstrating favorable change in FDG‐PET differences in rasagiline versus placebo in middle frontal ( P  < 0.025), anterior cingulate ( P  < 0.041), and striatal ( P  < 0.023) regions. Clinical measures showed benefit in quality of life ( P  < 0.04). Digit Span, verbal fluency, and Neuropsychiatric Inventory (NPI) showed non‐significant directional favoring of rasagiline; no effects were observed in Alzheimer's Disease Assessment Scale‐Cognitive Subscale (ADAS‐cog) or activities of daily living. Rasagiline was generally well tolerated with low rates of adverse events and notably fewer neuropsychiatric symptoms in the active treatment group. Discussion: These outcomes illustrate the potential benefits of rasagiline on clinical and neuroimaging measures in patients with mild to moderate AD. Rasagiline appears to affect neuronal activity in frontostriatal pathways, with associated clinical benefit potential warranting a more fully powered trial. This study illustrated the potential benefit of therapeutic repurposing and an experimental medicine proof‐of‐concept design with biomarkers to characterize patient and detect treatment response.